The Grimm legacy in portuguese children’s literature: the case of "Little Red Riding Hood" - Reis da Silva, Sara (Tropelías: Revista de Teoría de la Literatura y Literatura Comparada, 2015)
En Portugal, la difusión de los textos de los hermanos Grimm se inicia en el siglo XIX con la edición de obras infantiles como, por ejemplo, Contos para os nossos filhos (1882), de Maria Amália Vaz de Carvalho e Gonçalves Crespo, y con algunas traducciones de Henrique Marques Júnior para la «Biblioteca das Crianças» (1898-1910). La divulgación de versiones de Caperucita Roja fue también relevante en publicaciones periódicas. En realidad, en el contexto literario portugués, las reescrituras de esta narración – fuese con intenciones miméticas/imitativas, fuese con intenciones subversivas o paródicas – mantuvieron casi siempre el modelo tranquilizador germánico, como se refleja en los textos “O Chapelinho Encarnado” (in Contos para a Infância) (1877), de Guerra Junqueiro, o A Nau Catrineta e a Outra História do Capuchinho Vermelho (1967), de Alice Gomes. Narraciones contemporáneas potencialmente destinadas a niños y/jóvenes, como O Gorro Vermelho (2002), de Ana Saldanha, o A Menina do Capuchinho Vermelho no Século XXI (2007), de Luísa Ducla Soares, manifiestan la pervivencia de los efectos intertextuales nacidos del cuento clásico en cuestión. História do Capuchinho Vermelho contada a crianças e nem por isso (2005), de la autoría de Manuel António Pina, a partir de pinturas al óleo de Paula Rego, tiene como hipotexto, en cierta medida, la versión francesa de Perrault. Este ensayo se centra en los comienzos de la edición portuguesa de los cuentos de los hermanos Grimm, así como en el análisis de diversas narraciones actuales inspiradas en Caperucita Roja. In Portugal, the diffusion of Grimm’s texts began in the nineteenth century with children’s books as Maria Amália Vaz de Carvalho and Gonçalves Crespo’s Contos para os nossos filhos (1882) and some translations by Henrique Marques Júnior in «Biblioteca das Crianças» (1898-1910). The divulgation of versions of the “Red Riding Hood” was also important in periodical publications. In fact, within the Portuguese literary context, the rewritings of this narrative – either imitatively, subversively or parodically – have mostly followed the reassuring German model, as in, for example, Guerra Junqueiro’s “O chapelinho encarnado” (1877), or Alice Gomes (A Nau Catrineta e a Outra História do Capuchinho Vermelho, 1967). Contemporary children’s books such as Saldanha’s O Gorro Vermelho (2002) or Ducla Soares’ A Menina do Capuchinho Vermelho no Século XXI testify the survival of intertextual effects derived from the classic tale. História do Capuchinho Vermelho contada a crianças e nem por isso (2005), written by Manuel António Pina with works in pastel by Paula Rego, uses, to a certain extent, Perrault’s French version as ur-text, in keeping with the work of the referred artist. This paper focuses on the beginnings of Grimm’s fairy tale Portuguese editions, as well as on several contemporary narratives inspired by “Little Red Riding Hood”.